KEPASTIAN HUKUM ATAS HARTA BERSAMA SETELAH PERCERAIAN DALAM PERKAWINAN TIDAK TERCATAT MENURUT HUKUM ADAT TIONGHOA - stevany, stevany; Sagio, Ibrahim; Alhadiansyah, Alhadiansyah (Faculty Of Law, Universitas Tanjungpura, 2023)
AbstractThe authors raised the issue of legal certainty regarding the distribution of joint assets after a divorce based on Chinese customary law. In the provisions of Article 37 of Law Number 1 of 1974 which states that